(untitled) (European Journal of Economics, Finance and Business Development, 2023)
Tashkent traditionally occupies a special place in the economy of Uzbekistan. The capital is the core of Uzbekistan’s financial and credit system, powerful industrial production, and huge scientific and cultural potential. All this makes Tashkent a leader in economic development, the growth rate of these main economic indicators is higher than the average for Uzbekistan. The incomes of Tashkent hotel enterprises are stable and tend to grow. At the same time, the number of hotels in Tashkent is still very small compared to other European capitals. This article presents specific factors of competitiveness of small hotels, as well as customer-oriented strategies that allow small hotels that are part of a network of partners to significantly improve the quality of customer service and increase their profitability.